Trophic dynamics (Dissolved Inorganic Nitrogen-DIN and Dissolved Inorganic Phosphorus-DIP) in tropical urban estuarine systems during periods of high and low river discharge rates - CARLOS NORIEGA; MOACYR ARAUJO; MANUEL FLORES-MONTES; JULIA ARAUJO (Anais da Academia Brasileira de Ciências, 2019)
Abstract: This paper focused on the use of the biogeochemical LOICZ (Land Ocean Interactions in the Coastal Zone) to investigate the dynamics of DIN and DIP nutrients among three highly urbanized tropical estuaries (Barra das Jangadas (BJ), Recife (RE) and Timbó (TB)), located in the northeastern region of Brazil. The input data were obtained through in situ measurements (2007) and governmental agency databases (2001-2007). The balances of the non-conservative elements showed that the RE and TB systems alternated between sources and sinks during the observation periods (0.2-0.8 mmoles DIP m-2 d-1 and 0.1-10 mmoles DIN m-2 d-1). The metabolism rates in the systems indicated that the BJ system was autotrophic during the two observation periods (10-26 mmoles C m-2 d-1), while the RE system was heterotrophic (9-12 mmoles C m-2 d-1). The river discharge rates observed during the period 2001-2007 showed averages ranging from 9.4±3.8 to 18.4±7.7 m3s-1. Measurements of the trophic status in the RE system during 2007 characterized the system as eutrophic, thereby demonstrating high levels of chlorophyll-a and inorganic nutrients. The applications of balance sheets modeling proved to be very useful toward understanding the dynamics of estuarine systems dominated by large urban centers.